Telaah Terhadap Konsep Pembaharuan Pendidikan Islam Muhammad Abduh - Irwansyah Suwahyu (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2022)
This article examined Muhammad Abduh's renewed thinking in the field of Islamic education. This study was conducted to explain the importance of education in life through the thinking of one of the reformers in Egypt. This research was a library research in which data was obtained through documents analyzed by content analysis. The results of this study suggest that Islam strongly recommends that its adherents have a balance between mind and soul. This must be in the process of a person studying or studying. Where the community became imitation and did not want to accept technological advances in the West at that time. Muhammad Abduh also had a brilliant idea to renew the objectives, curriculum, methods of Islamic education that could be used as a reference in the education process.